New techno-functional approaches of gastroprotectors: both fermented milk and an exopolysaccharides produced by streptococcus thermophilus CRL1190 - Lobo, Rene Emanuel (2021)
Streptococcus (S.) thermophilus CRL1190 is a lactic acid bacteria (LAB) capable of producing high molecular weight exopolysaccharides (EPS1190) in skim mil. The LAB strain, the EPS1190, and the strain-fermented milk (FM1190) proved effective gastroprotective against gastric lesions of different etiology. Currently, we studied new beneficial aspects of these gastro-protectors agents of interest in the food industry. We isolated a polymer sugar from FM1190 with high purity and significant radical scavenging capacity. Moreover, both EPS1190 and FM1190 had excellent anti-constipation performance in an experimental animal model. Also, FM1190 maintained its microbiological quality during cold storage for 28 days. Finally, S. thermophilus CRL1190 survived and hydrolyzed the bile salts tested, although with lower hydrophobicity. For above, the starter culture, as well as its functional dairy food containing the novel exopolysaccharide, present strong potentialities to transfer in the dairy industry.